SPECIES DISTRIBUTION OF STYRAX SUMATRANA IN NORTH SUMATRA USING MAXENT MODELLING APPROACH - Saputra, Muhammad Hadi; Sagala, Saut Aritua Hasiholan; Lee, Han Soo (Universitas Muhammadiyah Surakarta, 2019)
Styrax sumatrana is the prestigious tree from North Sumatra. The resin which is a product from this tree has high demand and take a role as the primary income for farmer around the forest. However, the climate change along with the land conversion, threatens the species distribution . This paper aims to analyse the variable that contributes to Styrax sumatrana distribution and predict the potential distribution area of the species in North Sumatra Province . Several variables, such as elevation, slope, aspect, climate condition and land use land cover (LULC), were used to analyse the contribution for Styrax sumatrana distribution. The analysis uses the Maximum entropy model to examine the variable contribution for species distribution. The result shows that the mean temperature of the coldest quarter has a higher contribution for species distribution followed by elevation and LULC. The climate condition has a great impact by 28.5% than the other variable. The potential area that is suitable for Styrax sumatrana distribution was 8.91% or around 663,221.94 ha from a total of region.